Operational Risk Management and User Satisfaction as Drivers of Homestay Loyalty in Nglanggeran Tourism Village, Gunungkidul, Yogyakarta - Amin Kiswantoro; Sugiarto Sugiarto; Tonny Hendratono; Nur Rohman; Rizky Maulana (Asian Journal of Social and Humanities, 2025)
This study explores operational risk management in the context of homestays, a rapidly growing segment of the tourism industry. Specifically, the research aims to identify key operational risk management indicators tailored for homestays, focusing on homestay users in Nglanggeran Tourism Village, Gunungkidul, Yogyakarta, Indonesia. A total of 156 respondents, all with prior experience in the area, participated in the study, which employed multi-stage sampling and triangulated data collection methods. The research utilized an explanatory design, with data analyzed through Structural Equation Modeling (SEM). To complement the quantitative findings, in-depth interviews were conducted with homestay managers and participants. The study investigated three primary variables: operational risk management, user satisfaction, and user loyalty. The results show that effective operational risk management has a positive and significant impact on user satisfaction. Furthermore, user satisfaction is a key driver of user loyalty, as satisfied users are more likely to revisit and recommend the homestay to others. This study provides valuable insights into the role of operational risk management in enhancing user experience and fostering long-term customer loyalty in the homestay sector.